Strategi Implementasi Aplikasi Mobile KMS Sawit Rakyat Berbasis Rural Participatory - Tiana, Ade Hikma; Hermadi, Irman; Nurhadryani, Yani; Asfarian, Auzi; Kesuma, I Nyoman Rai Widartha (Departemen Ilmu Komputer, Institut Pertanian Bogor, 2023)
KMS Sawit Mobile Application has been developed since 2020 to enhance private palm oil farmers productivity by sharing its information to the other users. The first aim of this research is to implement the strategy of KMS Sawit Mobile Application for private palm oil farmers, secondly it is also to do usability testing of the application so that would be found the constraints when using the app. The methodology used in this research is by using implementation method – KM IRIS with PRA approach with usability testing in learnability, efficiency, and error aspects by giving some task scenarios. It is obtained from the research that the palm oil farmers are able to use and interact using the app. The measurement result of the usability testing showed that the learnability aspect point is 91.5%, the efficiency aspect point is 0.0864, and the error aspect point is 0,56 which is interpreted that the succession of palm oil farmers when using the app is above the average by solving the task swiftly and the number of errors they made is below the average. Therefore, based on that result it is showed that the KMS Sawit Mobile Application is can be used easily and fastly.